Perfil clínico, molecular e associação de polimorfismos nos genes XPD, PARP1 e em ilhas CPGs do gene SMO ao carcinoma mamário no estado da Paraíba - Santos, José Roberto Dantas de Andrade (2019)
Breast cancer (CM) is considered a multifactorial neoplasm related to genetic, epigenetic and environmental factors being the main cause of cancer among women. One of the main factors contributing to the risk of these tumors is genetic predisposition. Mutant alleles in BRCA1 or BRCA2 (BRCA) account for most of the hereditary susceptibility to breast cancer. Still, much of the genetic contribution to CM risk remains unknown. The molecular events involved in breast carcinogenesis are still poorly known and have revealed a wide variety of genetic alterations. Several studies establish the association of certain SNPs with different cancer cell behaviors in an attempt to determine specific molecular markers that may result in better screening, prevention, and therapeutic strategies for cancer patients. The aim of this study was to select variants in genes involved in DNA repair pathways and Hedgehog signaling pathways. SNPs rs1136410 in the PARP1 gene, rs565460302 in the XPD gene and rs538312246 in the SMO gene were genotyped in 100 paraffin tissue samples from patients diagnosed with breast cancer.The results were obtained by the Dideoxy Single Allele Specific method - DSASP. The Bioestart and R-studio software were used for the statistical analysis and application of the chi-square and Fisher’s exact test with a significance level of 5%. SNPs rs565460302 and rs538312246 showed no statistically significant association. However, the rs1136410 SNP showed a significant association (X2 = 100 and P <0.0001), thus suggesting a potential molecular marker.